82 TUMOR NECROSIS FACTOR α-INDUCED APOPTOSIS CONTRIBUTES TO THE PROGRESSION OF HEART FAILURE IN MICE AND CAN BE RESCUED BY D-4F TREATMENT. (1st January 2006) - Alvergue, J.; Chang, H.; Jordan, M.; Murdock, J.; Roos, K.; MacLellan, W. R.
Abstract : Background: Cardiac-specific overexpression of TNF-α in vivo produces a dilated cardiomyopathy. Studies in our lab have demonstrated that cardiac myocyte apoptosis is increased in TNF-α overexpressing transgenic (Tg) mice; however, TNF-α treatment alone does not increase apoptotic rates in cultured cardiac myocytes. We explored the effects of TNF-α on cultured cardiac myocytes expressing an apoptotic "sensitizer" (c-Myc) elevated in failing myocardium. The role of apoptosis in heart failure (HF) progression in TNF-α Tg mice was determined by treatment by D-4F, an apolipoprotein A-1 mimetic peptide that has been shown to favorably alter the inflammatory properties of HDL. Methods: Neonatal rat ventricular myocytes (NRVMs) were infected with an adenovirus overexpressing human c-Myc (AdMyc) or a virus expressing LacZ as a negative control (AdLacZ). Virus-infected cells were treated with 20 ng/μL TNF-α for 12 h and assessed for apoptosis by TUNEL staining. In vivo studies used wild-type (NTg) or Tg mice expressing human TNF-α in adult myocardium treated with D-4F or saline beginning at week 4 of life, and sacrificed at week 8. Hypertrophy was assessed by heart mass. Cardiac function was assessed by 2-D echo. Myocyte morphology was studied by H&E sectioning and apoptosis was quantified by TUNEL staining. Results: c-Myc overexpressing NRVMs treated with TNF-α showed a 2-fold increase in apoptosis compared to untreated c-Myc overexpressing myocytes ( p < .05). There was no significant difference in apoptosis between AdMyc infected cells not treated with TNF-α or TNF-α-treated AdLacZ infected cells and non-infected controls. In vivo, TNF-α Tg mice, when compared to NTg mice, demonstrated adverse LV remodeling (EDD 4.6 ± 0.2 mm vs 3.82 ± 0.26 mm, p < .05), reduced cardiac function (LVEF% 49.5 ± 15 vs 63.2 ± 9.3, p < .05), and increased cardiac hypertrophy measured by heart weight to body weight ratio (7.1 ± 0.02 vs 5.2 ± 0.47 mg/g, p < .01). Treatment with D4-F completely inhibited the adverse remodeling in TNF-α Tg mice and reduced apoptotic rates. Conclusions: TNF-α induces cardiac myocyte apoptosis in vitro when sensitized by c-Myc. TNF-α-induced LV remodeling and heart failure in mice is attenuated by treatment with D-4F, possibly through a reduction in cardiac myocyte apoptosis. These models will provide useful tools to explore the mechanisms of TNF-α action and beneficial effects of D-4F.